Law Enforcement Against Human Trafficking Through Migrant Workers - Achmad Yusuf (Journal of Strafvordering Indonesian, 2025)
Trafficking in persons through migrant-labor schemes has become an increasingly complex transnational crime in Indonesia. This study examines the effectiveness of law enforcement against trafficking in persons (TIP) committed under the guise of migrant worker placement. Using a normative and socio-legal approach, the research evaluates the adequacy of legal instruments, inter-agency coordination, and socio-economic dynamics influencing vulnerability to trafficking. Data were collected from primary legal sources, judicial decisions, official government reports, and international organizations monitoring migration and trafficking. The findings reveal that, despite Indonesia’s comprehensive legal framework under Law No. 21/2007 and Law No. 18/2017, alongside its commitment to the Palermo Protocol, implementation challenges persist. These include fragmented institutional coordination, limited cyber-investigation capacity, loopholes in administrative oversight, and socio-economic pressures that drive individuals to migrate irregularly. The study concludes that a holistic strategy combining penal, administrative, and community-based approaches is essential. Strengthening coordination between the National Police, BP2MI, Immigration, and the Ministry of Foreign Affairs, enhancing digital migration governance, and implementing community empowerment initiatives in migrant-sending regions are key to preventing exploitation and dismantling trafficking networks.